2002
DOI: 10.1103/physrevlett.88.237001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Structures of Chain Vortices Inside Anisotropic High-TcSuperconductors

Abstract: In order to elucidate the formation mechanism of unconventional arrangements of vortices in high- Tc superconducting thin films at an inclined magnetic field to the layer plane, we investigated the structures of vortex lines inside the films by Lorentz microscopy using our 1-MV field-emission electron microscope. Our observation results concluded that vortex lines are tilted to form linear chains in YBaCu3O(7,8). Vortex lines in the chain-lattice state in Bi2Sr2CaCu2O(8+delta), on the other hand, are all perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 14 publications
2
32
1
Order By: Relevance
“…In the case of YBaCu 3 O 7.8 , the conclusion is evident from the obtained Lorentz micrographs (64) in Fig. 11.…”
Section: Winding Vortex Lines In High-t C Superconductorssupporting
confidence: 72%
See 1 more Smart Citation
“…In the case of YBaCu 3 O 7.8 , the conclusion is evident from the obtained Lorentz micrographs (64) in Fig. 11.…”
Section: Winding Vortex Lines In High-t C Superconductorssupporting
confidence: 72%
“…An electron wave was incident on a tiny toroidal sample, and the phase difference ⌬ between 350-kVFEEM(5) 5 ϫ 10 9 Dynamic observation of vortices in metal superconductors (7) 2000 1-MV FEEM(6) 2 ϫ 10 10 Observation of unusual behaviors of vortices in high-Tc superconductors (8,64,65) 11,000 (9) TEEM, thermal-emission electron microscope; FEEM, field-emission electron microscope. …”
Section: The Ab Effectmentioning
confidence: 99%
“…(67)- (68) Recently, Garadoc-Daries et al [68], Matthews et al [69] and Madison et al [70] observed vertex solitons in the Boson-Einstein condensates. Tonomure [71] observed experimentally magnetic vortexes in superconductors. These vortex lines in the type-II-superconductors are quantized.…”
Section: Properties Of Macroscopic Quantum Effects and Dynamic Naturementioning
confidence: 99%
“…In a finite solenoid stray field leaks near the ends, reducing the overall energy since less flux is enclosed by the current. The energy of a finite solenoid can be written as the energy of a long solenoid multiplied by a correction factor, K(R), called the Nagaoka factor [35,36] as shown in equation (25). A approximation for the Nagaoka factor correct to 6 significant figures which is straightforward to implement is given in ref.…”
Section: Orientation Of Flux Vortices In Thin Samplesmentioning
confidence: 99%
“…The microscope has a liquid helium cooled in-column specimen stage equipped with coils to allow magnetic fields to be applied to the sample at any angle. This proved useful in the investigation of stacks of pancake vortices in YBCO (YBa 2 Cu 3 O 7-δ ) which apparently broke into several stacks as the angle at which the field was applied increased [25].…”
mentioning
confidence: 99%